Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/ismej.2015.240
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal determinations of algal virus decay rates reveal overwintering in a temperate freshwater pond

Abstract: To address questions about algal virus persistence (i.e., continued existence) in the environment, rates of decay of infectivity for two viruses that infect Chlorella-like algae, ATCV-1 and CVM-1, and a virus that infects the prymnesiophyte Chrysochromulina parva, CpV-BQ1, were estimated from in situ incubations in a temperate, seasonally frozen pond. A series of experiments were conducted to estimate rates of decay of infectivity in all four seasons with incubations lasting 21 days in spring, summer and autum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 85 publications
2
26
0
Order By: Relevance
“…That Microcystis blooms can proliferate to massive densities [ 61 ] and yet somehow escape infection by the community of abundant phage [ 62 ] remains a perplexing ecological problem. This may be explained by the ability to resist infection by lytic viruses due to lysogen-induced resistance to superinfection.…”
Section: Discussionmentioning
confidence: 99%
“…That Microcystis blooms can proliferate to massive densities [ 61 ] and yet somehow escape infection by the community of abundant phage [ 62 ] remains a perplexing ecological problem. This may be explained by the ability to resist infection by lytic viruses due to lysogen-induced resistance to superinfection.…”
Section: Discussionmentioning
confidence: 99%
“…(No Pbi viruses were detected in this study). Even in low-viral-abundance months, infectious chlorovirus populations were maintained, suggesting either that the viruses are very stable [224] or that there is ongoing viral production in natural hosts. It is unknown if chloroviruses replicate exclusively in zoochlorellae symbiotic with paramecia and heliozoae or if the viruses have another host(s).…”
Section: Natural History Of the Chlorovirusesmentioning
confidence: 99%
“…burst size or length of infection cycle) of viral infections and decay rates of free virus particles modulate the dynamics of the host viral system. Many studies in the laboratory and the environment have shown certain environmental factors cause increased viral decay rates although these are virus specific [16,17], but how the changing environment influences the infection cycle within a cell is less understood. Abiotic factors such as irradiance level [18,19], temperature [20], and nutrients [21] have been shown to negatively influence the infection cycle dynamics in various algal virus systems.…”
Section: Introductionmentioning
confidence: 99%